2016
DOI: 10.1111/conl.12280
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Benefits of Large Carnivore Recolonization Through Reduced Wildlife‐Vehicle Collisions

Abstract: The decline of top carnivores has released large herbivore populations around the world, incurring socioeconomic costs such as increased animal–vehicle collisions. Attempts to control overabundant deer in the Eastern United States have largely failed, and deer–vehicle collisions (DVCs) continue to rise at alarming rates. We present the first valuation of an ecosystem service provided by large carnivore recolonization, using DVC reduction by cougars as a case study. Our coupled deer population models and socioe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 25 publications
(70 reference statements)
0
68
0
Order By: Relevance
“…Like many other large carnivores, cougars are periodically involved in conflicts with livestock producers and rural residents (Gilbert et al. ). Wildlife professionals also frequently feel considerable pressure to reduce large carnivore populations in an effort to bolster ungulate populations (Todd , Hurley et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like many other large carnivores, cougars are periodically involved in conflicts with livestock producers and rural residents (Gilbert et al. ). Wildlife professionals also frequently feel considerable pressure to reduce large carnivore populations in an effort to bolster ungulate populations (Todd , Hurley et al.…”
Section: Discussionmentioning
confidence: 99%
“…Large carnivores are controversial species whose management and conservation are complicated by broader psychological, political, and socioeconomic issues (Treves and Karnath 2003, Chapron et al 2014, Ripple et al 2014. Like many other large carnivores, cougars are periodically involved in conflicts with livestock producers and rural residents (Gilbert et al 2016). Wildlife professionals also frequently feel considerable pressure to reduce large carnivore populations in an effort to bolster ungulate populations (Todd 2002, Hurley et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the potential impact of large predator presence on the effect of Red Fox and corvids on small game species is a research priority given the economic costs associated with predator control and the potential benefits in terms of conservation arising from changes in gamekeeper attitudes towards raptors (Red Fox and Eurasian Magpie Pica pica are the two main species targeted by predator control in Spain and also regular prey of several species of large eagles and of the Eagle-Owl). Similarly, in a recent study, Gilbert et al (2016) revealed that recolonizing Cougars Puma concolor could reduce deer densities and deer-vehicle collisions by 22% in the Eastern United States, preventing 21 400 human injuries, 155 fatalities and $2.13 billion in avoided costs within 30 years of establishment.…”
Section: Future Research Directions Combining Experimental and Long-tmentioning
confidence: 93%
“…More studies using the same approach as Gilbert et al (2016), coupling mesopredator population models to socio-economic valuation in order to assess the ecosystem services provided by large raptors through reduction in impact of mesopredators (through either direct trophic cascades or behaviourally mediated effects) on decreasing and economically important game species, would be extremely valuable.…”
Section: Future Research Directions Combining Experimental and Long-tmentioning
confidence: 99%
“…In the United States alone, over a million vertebrates are killed per day as a result of vehicle collisions (Forman and Alexander 1998). In addition to directly reducing wildlife populations and compromising habitat connectivity by limiting animal movement (Hanski 1999, Coffin 2007, Crooks et al 2011, wildlife-vehicle collisions also present a high cost to society (Gilbert et al 2016). Across the state of California, USA, collisions with wildlife result in nearly 300 injuries to people and >5 human deaths/year and >$130 million in property damage (Shilling 2016).…”
mentioning
confidence: 99%